(untitled) (Communications in Computational Physics, 2020)
Effective medium methods for the attribution of micro-structures to macro elastic properties of shales are important for the prediction of sweet spots in the shale-gas production. With X-ray micro-computed tomography (XMCT), the micro-structures of shale core samples from Longmaxi Formation are visualized and characterized by 3D digital images. As an efficient alternative to conventional effective medium methods for estimating elastic properties, we propose a consistent workflow of lattice spring modeling (LSM) to emulate the digital cores using three types of lattices. Particular attention is paid to investigate the effective Young's moduli, Poisson's ratios, and preferred orientations, by uniaxial compression tests along two directions. Within elastic deformation, the impact of lattice arrangements on the anisotropy is even more than those of stress disturbances and micro-structural features. Compared with analytical approximations and theoretical predictions, the LSM numerical scheme shows general applicability for heterogeneous porous rocks.